A fluorometric assay platform for caffeic acid detection based on the G-quadruplex/hemin DNAzyme. Issue 14 (24th May 2016) - Cai, Nan; Li, Yan; Chen, Shufan; Su, Xingguang
Abstract : A fluorometric assay platform based on GQDs is designed for biochemical detection of caffeic acid. Abstract : In this paper, a fluorometric assay platform for fluorescence detection of caffeic acid was designed based on the peroxidase-mimicking activities of G-quadruplex/hemin DNAzyme. Under the catalysis of the formed G-quadruplex/hemin complex, H2 O2 could be decomposed into hydroxyl radicals with strong oxidation properties. Then caffeic acid would be oxidized by the released hydroxyl radicals, resulting in the product caffeic acid–quinone. Normally, caffeic acid has no influence on the fluorescence of graphene quantum dots. But when mixed with the G-quadruplex/hemin complex and H2 O2, the fluorescence of graphene quantum dots was obviously quenched by the oxidized caffeic acid. Under the optimized experimental conditions, the quenched fluorescence intensity was linearly correlated with the concentration of caffeic acid, ranging from 2 μM to 350 μM with a detection limit of 200 nM. The proposed method was applied to the determination of caffeic acid in human serum samples with satisfactory results.